Effect of Supplementation of Tanshinone IIA and Sodium Tanshinone IIA Sulfonate on the Anticancer Effect of Epirubicin: An In Vitro Study. (24th May 2011) - Chan, Szu-Erh; Lai, Hung-Wen; Su, Chin-Cheng; Kuo, Shou-Jen; Chien, Su-Yu; Lin, Hui-Yi; Chen, Dar-Ren
Abstract : Tanshinone IIA (Tan IIA) and sodium tanshinone IIA sulfonate (STS) were found to have protective effects on cardiomyocyte against adriamycin-induced damage and may be used clinically. It is unclear whether the supplementation of STS or Tan IIA would affect the anticancer activity of anthracycline. To evaluate the effect of Tan IIA or STS on the anticancer of epirubicin, the cell viability, apoptosis, Akt expression, and uptake of epirubicin after supplementation of Tan IIA or STS in the epirubicin-treated BT-20 cells were measured and compared. Tan IIA inhibited BT-20 cell growth and induced apoptosis in a time- and dose-dependent manner. When Tan IIA was used with epirubicin, an increase of BT-20 cells apoptosis was accompanied by the decreasing phosphorylation of Akt. STS had no effect on the cell viability of BT-20 cells. However, when used with epirubicin, STS decreased the epirubicin-induced cytotoxicity and apoptosis in BT-20 cells. The antagonistic effect of STS on epirubicin-induced cytotoxicity in BT-20 cells occurred concomitantly with the reduced epirubicin uptake and the increased phosphorylation of Akt. STS decreased the uptake of epirubicin in BT-20 cells and blocked epirubicin-induced apoptosis through activation of Akt.